Evaluation of minimally invasive estrus synchronization protocols in brown brocket deer (Subulo gouazoubira) - Ferrari, Bianca [UNESP]; Galindo, David Javier [UNESP]; Gimenes, Lindsay Unno [UNESP]; Duarte, José Maurício Barbanti [UNESP] (Elsevier, 2023)
This study aimed to evaluate minimally invasive protocols for estrus synchronization in the brown brocket deer (Subulo gouazoubira). Females were submitted to Latin square design, in different treatments. All females received 0.25 mg of estradiol benzoate on the first day of treatment, concomitant with one of the following sources of progesterone: (1) DIP: an intravaginal progesterone releasing device for eight days, (2) MGA1x: once a day (in the morning) oral dose of 1 mg melengestrol acetate for eight days, (3) MGA2x: twice a day (morning and afternoon) oral doses of 0.5 mg of MGA for eight days, (4) P4LA: a single i.m. administration of 75 mg of long-acting progesterone (P4LA). Eight days after the beginning of each treatment, females received an i.m. administration of 265 µg of prostaglandin (PGF2α; cloprostenol). Treatment efficacy was evaluated by manifestation of behavioral estrus after treatment and concentration of fecal progesterone metabolites (FPM). The time to onset of estrus in treatment P4LA was significantly longer (180 ± 38.9 h) compared to DIP (63 ± 6.6 h), MGA1x (53 ± 14.4 h) and MGA2x (41 ± 10.1 h) (P = 0.008). According to individual baseline FPM and FPM concentration during the days after estrus, the corpus luteum formation was suggested in all females which responded to the treatments (93.75 %). Low synchrony, longer interval between PGF2α administration and onset of estrus suggest that the P4LA dose (75 mg) is too high and not effective for S. gouazoubira. DIP, MGA 1x and MGA 2x, were effective in estrus synchronization.
Keywords: Enzyme immunoassay; Fecal progesterone metabolites; Long-acting progesterone; Melengestrol acetate; Neotropical deer